Research oriented ground improvement projects in Changi, Singapore - M. W. Bo; A. Arulrajah; V. Choa; S. Horpibulsuk (Lowland Technology International, 2018)
The Changi East Reclamation projects in Singapore were implemented under 5 Phases commencing from 1991 and completed in 2005 with one phase to another has several of years of overlapping. The total implementation period was 15 years including maintenance. The Phases are named as Phase 1A, 1B, 1C, Area A (North) and Area A (South). Each Phase took about 5 to 6 years to implement. Due to the involvement of large area fills in the form of land reclamation with as thick as nearly 20 meters of hydraulic fills over up to 40 meters thickness of compressible marine clay, significant challenges were present to the geotechnical engineers on geotechnical issues such as slope stability, consolidation settlement and liquefaction potential. Due to the excessive magnitude of settlement likely to occur over a long period of duration caused by consolidation process, extensively large area was required to improve applying ground improvement methods to accelerate the consolidation process. Therefore, a good design of accelerating consolidation process by applying ground improvement method was deemed necessary. Many combinations of pilot tests were implemented to verify the design of ground improvement works. In addition to improving the underlying soils, improvement was also required for the fills which were loosely deposited by means of hydraulic filling techniques. In order to be able to successfully implement these complex projects, applying the most up to date state of the art technologies, implementation of research level planning, investigation, design and implementation processes were required throughout the projects from master planning stage to commissioning stage. Several forms of performance monitoring using geotechnical instrumentation, verification of achieving specified improvement using intermediate and post improvement ground investigation and in-situ testing were implemented during and acceptance of ground improvement works. Quality control and assurance tests of material delivered and used for ground improvement were carried out throughout the implementation process. This paper presents how research oriented ground improvement projects were implemented in the past decade in Singapore.